Rambler Dreams. Poesía y modernidad en la Costa Norte de Honduras - Alvarado, Leonel (Oltreoceano - Rivista sulle migrazioni, 2021)
A la ya conocida influencia política, militar y económica de los Estados Unidos en Honduras, que comienza durante el incipiente proceso de modernización decimonónico, se añade un imaginario cultural y literario al que han respondido varios escritores, sobre todo de la costa norte del país. En este ensayo se analiza la forma en que ese imaginario se refleja en algunos poemas de José González. Rambler Dreams. Poetry and Modernity on the North Coast of Honduras In response to the well-known political, military and economic influence of the United States in Honduras, which began with the process of modernization in the 19th century, there has been a cultural and literary movement comprising many writers, especially from the North Coast of the country, have responded. This essay analyzes the way in which this imaginary is reflected in some of José González’s poems.